Pengaruh Instagram dan Kualitas Layanan Terhadap Keputusan Pembelian Jasa Wedding Event Pada The Solution Event Management Medan - Margaretha, Maria; Siregar, Efni (Abdimas Indonesian Journal, 2025)
This study aims to determine the effect of Instagram and service quality on purchasing decisions for wedding event services at The Solution Event Management. This study uses a quantitative approach with data collection methods by distributing questionnaires. In this study using Purposive Sampling technique (Purposive or Judgment Sampling). The sample in this study were users of The Solution Event Management services, totalling 80 respondents. Measurement in this questionnaire uses a Likert scale of 1 to 5. Hypothesis testing in this study uses multiple linear regression models with multiple linear regression tests using multiple linear regression models with simultaneous tests, partial tests, the coefficient of determination and supported by the SPSS 27 programme. The results of the study prove that social media has a positive but not significant effect on purchasing decisions and service quality has a positive and significant on purchasing decisions for wedding event services at The Solution Event Management Medan. Instagram and Service Quality have a positive and significant effect together on purchasing decisions for wedding event services at The Solution Event Management Medan. Instagram and Service Quality have a positive and significant effect together on purchasing decisions for wedding event services at The Solution Event Management Medan by 12.7% and the remaining 87.3% can be explained by factors not examined in this study.